2009
DOI: 10.3390/s90907498
|View full text |Cite
|
Sign up to set email alerts
|

Platform for a Hydrocarbon Exhaust Gas Sensor Utilizing a Pumping Cell and a Conductometric Sensor

Abstract: Very often, high-temperature operated gas sensors are cross-sensitive to oxygen and/or they cannot be operated in oxygen-deficient (rich) atmospheres. For instance, some metal oxides like Ga2O3 or doped SrTiO3 are excellent materials for conductometric hydrocarbon detection in the rough atmosphere of automotive exhausts, but have to be operated preferably at a constant oxygen concentration. We propose a modular sensor platform that combines a conductometric two-sensor-setup with an electrochemical pumping cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Varhegyi et al [ 202 ] investigated the influence from corrosive gases such as Cl 2 and SO 2 on the Ga 2 O 3 -sputtered layer and found that Ga 2 O 3 was more resistant against SO 2 but had a very fast reaction with Cl 2 at 800 °C. A screen-printing technique was developed by Frank et al [ 188 ], Pole et al [ 201 ], Wiesner et al [ 195 ], and Biskupski et al [ 196 ] to prepare porous Ga 2 O 3 thick films for detecting oxidizing gases such as CO 2 and O 3 and inflammable gases such as C 4 H 10 and C 3 H 8 , as well as VOCs. Additionally, many other groups such as Macri et al [ 72 ], Ogita et al [ 62 , 63 , 97 , 103 ], Hovhannisyan et al [ 203 ], Dyndal et al [ 204 ], Almaev et al [ 86 , 87 ], Manandhar et al [ 101 ], and Sui et al [ 64 ] studied the gas sensitivities of resistor sensors with sputtering films for O 2 , H 2 , CO, C 7 H 8 , C 2 H 6 O, and C 3 H 6 O.…”
Section: Ga 2 O 3 -Based Gas Se...mentioning
confidence: 99%
“…Varhegyi et al [ 202 ] investigated the influence from corrosive gases such as Cl 2 and SO 2 on the Ga 2 O 3 -sputtered layer and found that Ga 2 O 3 was more resistant against SO 2 but had a very fast reaction with Cl 2 at 800 °C. A screen-printing technique was developed by Frank et al [ 188 ], Pole et al [ 201 ], Wiesner et al [ 195 ], and Biskupski et al [ 196 ] to prepare porous Ga 2 O 3 thick films for detecting oxidizing gases such as CO 2 and O 3 and inflammable gases such as C 4 H 10 and C 3 H 8 , as well as VOCs. Additionally, many other groups such as Macri et al [ 72 ], Ogita et al [ 62 , 63 , 97 , 103 ], Hovhannisyan et al [ 203 ], Dyndal et al [ 204 ], Almaev et al [ 86 , 87 ], Manandhar et al [ 101 ], and Sui et al [ 64 ] studied the gas sensitivities of resistor sensors with sputtering films for O 2 , H 2 , CO, C 7 H 8 , C 2 H 6 O, and C 3 H 6 O.…”
Section: Ga 2 O 3 -Based Gas Se...mentioning
confidence: 99%
“…Therefore, a second sensor has to be placed upstream of the catalyst, allowing determining the conversion by taking into account the signal of the two gas sensors. Of special interest are hydrocarbon sensors, for which many approaches have been reported in literature [4][5][6][7][8][9][10][11][12][13][14][15]. However, up to now, none of these principles has been serialized.…”
Section: Introductionmentioning
confidence: 99%